PENGARUH KARAKTERISTIK AUDITOR DAN JENIS USAHA KLIEN PADA RENTANG WAKTU PENYELESAIAN AUDIT - Rustiarini, . (Jurnal Ilmiah Akuntansi dan Bisnis, 2013)
ABSTRACT Timeliness of financial statements publication or referred to audit delay is the length  of the completion time of the audit as measured from the date of the closing fiscal year until the date of the issuance of audit reports. This research aimed to investigate the effect of auditor characteristics (age, education level, experience) and type of client business on the length of audit completion. Sample of this research were auditor in public accountant offices in Bali on 2012. Data was collected by questionnaire and was analyzed with multiple regression analysis. The results of this research showed that independent variable variation can be explained by audit delay about 53,2 percent. F-test showed that the model of regression can be used for estimating audit delay. Examination of hypothesis indicated that age, education level, and type of client business did not have significant effect on audit delay, but experience had significant effect on audit delay. Keywords: auditor characteristics, timeliness, type of client business